Concluding remarks: next generation nanoelectrochemistry – next generation nanoelectrochemists. (1st March 2022) - Unwin, Patrick
Abstract : This paper describes the scientific journey taken through electrochemistry to arrive at present-day nanoelectrochemistry and considers how the area might develop in the future, particularly in light of the papers presented at this Faraday Discussion . Abstract : The aim of this paper is to describe the scientific journey taken to arrive at present-day nanoelectrochemistry and consider how the area might develop in the future, particularly in light of papers presented at this Faraday Discussion . By adopting a generational approach, this brief contribution traces the story of the nanoelectrochemistry family within the broader electrochemistry field, with a focus on scientific capability and themes that were important to each generation. I shall consider research questions and the impact of technology that was developed or available in each period. Nanoelectrochemistry is still somewhat niche, but is attracting increasing numbers of researchers. It is set to become a major part of electrochemistry and interfacial science. It is studied by people with a fairly unique skillset, and I shall speculate on the skills and expertise that will be needed by nanoelectrochemists to address the challenges and opportunities that lie ahead. I conclude by asking: who will be the nanoelectrochemists of the future and what will they do?